2004
DOI: 10.1021/la048075u
|View full text |Cite
|
Sign up to set email alerts
|

Photosystem I Patterning Imaged by Scanning Electrochemical Microscopy

Abstract: We report the first directed adsorption of Photosystem I (PSI) on patterned surfaces containing discrete regions of methyl- and hydroxyl-terminated self-assembled monolayers (SAMs) on gold. SAM and PSI patterns are characterized by scanning electrochemical microscopy (SECM). The insulating protein complex layer blocks the electron transfer of the SECM mediator, thereby reducing the electrochemical current significantly. Uniformly and densely packed adsorbed protein layers are observed with SECM. Pattern images… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 41 publications
0
41
0
Order By: Relevance
“…The PSI attaches to the hydroxyl-terminated surface by hydrogen bonding. Inspired by Greenbaum et al's report on the preferred orientation of PSI on short-chained hydroxyl-terminated monolayers (e.g., HSC 2 OH) [5], we believe that PSI should adsorb similarly on a better packed SAM (e.g., HSC 6 OH for our studies), because the terminal group was shown to control the orientation of the protein. Our previous work shows that we can form compact PSI monolayers on HSC 6 OH SAMs [6], and that might lead to enhanced electrochemical signals, which we now present.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…The PSI attaches to the hydroxyl-terminated surface by hydrogen bonding. Inspired by Greenbaum et al's report on the preferred orientation of PSI on short-chained hydroxyl-terminated monolayers (e.g., HSC 2 OH) [5], we believe that PSI should adsorb similarly on a better packed SAM (e.g., HSC 6 OH for our studies), because the terminal group was shown to control the orientation of the protein. Our previous work shows that we can form compact PSI monolayers on HSC 6 OH SAMs [6], and that might lead to enhanced electrochemical signals, which we now present.…”
Section: Introductionmentioning
confidence: 82%
“…The chemicals were purchased as follows: Na 4 6 , K 4 Fe(CN) 6 AE 3H 2 O, acetone, and methylene chloride from Fisher Scientific; 8-bromo-1-octanol, 11-mercapto-1-undecanol (HSC 11 OH), 3-mercaptopropionic acid (HSC 2 COOH), and EDTA from Aldrich Chemical; 1-dodecanethiol (HSC 11 CH 3 ), 2-mercaptoethanol (HSC 2 OH), 1-hexanethiol (HSC 5 CH 3 ), 2-aminoethanethiol hydrochloride (HSC 2 NH 2 ), methyl viologen dichloride hydrate (MVCl 2 , or MV 2+ ), sorbitol, ascorbic acid, thiourea, Triton X-100, HEPES, Tricine, and tris(hydroxymethyl)aminomethane DNase, RNase, Protease free (TRIS) from Acros; Na 2 HPO 4 AE 7H 2 O, sodium ascorbate, N-(2-mercaptopropionyl)-glycine (HSCH(CH 3 )-CONHCH 2 COOH, tiopronin), DL-dithiothreitol from Sigma; H 2 SO 4 and NaOH from EM Science; ethanol (absolute proof) from Aaper; hydroxylapatite fast-flow from Calbiochem; 4-mercapto-1-butanol (HSC 4 OH) and 6-mercapto-1-hexanol (HSC 6 OH) from Fluka; N 2 from Gibbs Welding Supply. All chemicals were used as received unless otherwise specified.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PSI complexes were purifi ed by centrifugation at 20 000 g followed by column chromatography using a chilled hydroxylapatite column. [ 21 ] Excess surfactants and salts were removed using dialysis at a 1:2000 extract to water ratio. [ 9 ] The concentration of the resulting PSI solution was 7 × 10 −6 M with a chlorophyll concentration of 0.3 mg mL -1 as characterized by the methods of Porra [ 22 ] and Baba et al [ 23 ] Preparation of Reduced Graphene Oxide : Highly concentrated graphene oxide (graphene-supermarket.com) with an average fl ake size of 0.6-5 µm was diluted to a concentration of 0.1 mg mL -1 .…”
Section: Introductionmentioning
confidence: 99%
“…ð6Þ Next to feedback mode-based SECM [298], KFM is very useful for imaging the result of the patterning process, because in parallel to imaging it can be used to determine the electrical properties of the modified interface. It is based on determination of the surface potential of SAM-modified surfaces arising from the asymmetric electrical field that exists at the interface between two phases.…”
Section: Self Assembled Monolayersmentioning
confidence: 99%